Decision Support System For Selection Of Candidate Employees In Installation Section Using Multi-Objective Optimization Method By Ratio Analysis - bagaskara, dimas bima; Arief, Rachman (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2025)
Installation work is one of the most important aspects of building communication networks in companies such as PT. Telkom. The Telkom branch office in Bondowoso is currently experiencing a shortage of staff in the network installation department. Therefore, PT. Telkom Bondowoso branch is opening job vacancies for installation staff to quickly address the issue of internet network installation requests. This study aims to assist the Telkom Bondowoso branch in selecting prospective employees using the Multi-Objective Optimization by Ratio Analysis (MOORA) method. This method can simplify the selection process for the Telkom Bondowoso branch as it is systematically or hierarchically structured. The data collection method used in this study was interviews with representatives of the Telkom Bondowoso branch. The results of the needs analysis were then used as the basis for designing an efficient system. The MOORA method includes several steps, such as system requirements, system design, implementation, and testing. The criteria used in this study include the candidate's name, criteria values, and sub-criteria values. With a system accuracy result of 100%, it can be concluded that this system works well in selecting prospective employees.Keywords: Prospective Employees, Telkom Bondowoso Branch, MOORA